Comprehensive Review of Nurses’ Role in Chronic Disease Management: Collaborative Care Approaches - Al aateibi, Bader Shgaa; Sadoun, Manal Mohammed; Alnuaimi, Noora Rabeea; Alghamdi, Suad Abdaullah Saleh; Alharthi, Mesfer Fahad Awaidh; Khayat, Hafsah Mohammed; Almatrafi, Raghad Jameel Saleh; falattah, Miad Mohammed Bakor; Althobaiti , Abdullah Mohammed; Albariqi, Nabilah Ahmed Amer; Saeed, Nouf Ali (Journal of Ecohumanism, 2024)
Diabetes, hypertension, and heart diseases, as well as others, are common diseases that affect a large number of people around the globe today. Such diseases call for rational and integrated approaches across specialists to achieve the best patient results. Chronic illness care involves education of the patients, effective coordination of care, and management of symptoms, which are major areas that involve the input of the nurses. This review focuses on nursing interventions in chronic disease and the importance of the collaborative care model in nursing. Therefore, observing how the incorporated nursing skills in an interdisciplinary process influence the quality of patients’ lives with chronic diseases, the review examines the communication processes, evidence-based practice, and patient-centered approach. Highlights focus on the benefits of the involvement of nurses, including effective disease management, increased patient satisfaction, and improved health. The review also discusses the hurdles of nursing as a profession, such as having to contend for resources and emphasizing the continuous development of professional skills, before it presents specific recommendations for enhancing nursing stakeholders’ contributions to managing chronic diseases.